Why is loving a thief not the same as loving all men for the Mohists?. Issue 3 (3rd July 2018) - Chong, Chaehyun
ABSTRACT: The purpose of this article is to explain the Mohists' perceived inconsistences of the following three propositions in the Mojing since we attribute to them an unconditional love toward human beings: (A) A thief is a man. Killing a thief is not killing men. (B) A thief is a man. Loving a thief is not loving men. (C) Zang is a man. Loving Zang is loving men. The attribution of unconditional love toward human beings is not unusual to the Mohists when we render the Mohist idea of jian'ai as universal love. My interpretation first suggests that we can consistently interpret the Mohist ethical position as intentional utilitarianism. Second, I claim that Mohist universal love includes some generality, though it does not have to mean universality without exception. This Mohist generality will be explained through the generic use of nouns.